2017
DOI: 10.1186/s12985-017-0722-8
|View full text |Cite
|
Sign up to set email alerts
|

Muscovy duck reovirus σNS protein triggers autophagy enhancing virus replication

Abstract: BackgroundMuscovy duck reovirus (MDRV) causes high morbidity and mortality in Muscovy ducklings at 10 days old and can persist in an infected flock until the ducklings of 6 weeks old. It shares common physicochemical properties with avian reovirus (ARV) and differs in coding assignment and pathogenicity. The ARV p17 protein has been shown to trigger autophagy via activation multiple signaling pathways, which benefits virus replication. Since MDRV lacks the p17 protein, whether and how MDRV induces autophagy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…MDRV could cause injury of the small intestinal mucosal immune barrier and mucosal immune function in sick Muscovy ducklings ( Wu et al, 2017b ). MDRV σNS protein could trigger autophagy to enhance its replication ( Wu et al, 2017a ). The current study revealed that MDRV could induce ER stress and that p10.8 protein was the critical factor; these results provided new evidence for elucidating the molecular pathogenic mechanism of MDRV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MDRV could cause injury of the small intestinal mucosal immune barrier and mucosal immune function in sick Muscovy ducklings ( Wu et al, 2017b ). MDRV σNS protein could trigger autophagy to enhance its replication ( Wu et al, 2017a ). The current study revealed that MDRV could induce ER stress and that p10.8 protein was the critical factor; these results provided new evidence for elucidating the molecular pathogenic mechanism of MDRV.…”
Section: Discussionmentioning
confidence: 99%
“…The DF1 cell line was grown in Dulbecco’s modified Eagle’s medium (DMEM), supplemented with 10% FBS. Cells, at 70% confluence were transfected with plasmids (pCI-neo-flg, pCI-neo-flg-p10.8) using Lipofectamine 2000 reagent (Promega, Madison, WI, United States), as previously described ( Wu et al, 2017a ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a great deal of research into the relationship between viral infection and host autophagy. Autophagy commonly serves as a defense mechanism against viral infection [ 12 , 13 ]; however, many viruses have evolved to escape, or even to exploit, this mechanism to favor their survival or replication in different ways [ 6 , 14 , 15 , 16 , 17 ]. Thus, the role of autophagy in host-virus interactions is diverse for different viruses.…”
Section: Introductionmentioning
confidence: 99%